Fotogramas Queer: histórias abjetas no cinema - PEREIRA, Rodolfo Gomes (2024)
This paper aims to reflect on the Queer cinema, about how abject people are treated on the screen, using mainly theoretical concepts of Michel Foucault and Judith Butler. A time line is drawn by analyzing the movies with LGBTQ+ characters, linking them with important historical events for the queer movement. We concentrate on the films The Way He Looks (Hoje Eu Quero Voltar Sozinho), directed by Daniel Ribeiro launched in 2014, and Beautiful Thing, directed by Hettie MacDonald released in 1996. Both films talk about the discovery of homosexuality in adolescence which creates a interesting view point to explore how it affects the representation of the characters. The 18-year difference is important also to show the changes that have occurred throughout history in how abject people are treated.